Molecular Detection of Virulence Factors in Salmonella serovars Isolated from Poultry and Human Samples - Kelly Johanna Lozano-Villegas; María Paula Herrera-Sánchez; Mónica Alexandra Beltrán-Martínez; Stefany Cárdenas-Moscoso; Iang Schroniltgen Rondón-Barragán (Veterinary Medicine International)
Salmonellosis is a common infectious disease in humans caused by Salmonella spp., which in recent years has shown an increase in its incidence, with products of avian origin being a common source of transmission. To present a successful infective cycle, there are molecular mechanisms such as virulence factors that provide characteristics that facilitate survival, colonization, and damage to the host. According to this, the study aims to characterize the virulence factors of Salmonella spp. strains isolated from broilers (n = 39) and humans (n = 10). The presence of 24 virulence genes was evaluated using end-point PCR. All the strains of Salmonella spp. isolated from broiler chickens revealed presence of 7/24 (29, 16%) virulence genes (lpfA, csgA, sitC, sipB, sopB, sopE, and sivH). Regarding the strains isolated from cases of gastroenteritis in humans, all strains contained (14/24, 58, 33%) virulence genes (lpfA, csgA, pagC, msgA, spiA, sitC, iroN, sipB, orgA, hilA, sopB, sifA, avrA, and sivH). In summary, the presence of virulence genes in different strains of Salmonella isolated from broilers and humans could be described as bacteria with potential pathogenicity due to the type and number of virulence genes detected. These findings are beneficial for the pathogenic monitoring of Salmonella in Colombia.